THE ROLE OF CONVERSATIONAL AI TOOLS, LIKE CHATGPT, IN ENHANCING LANGUAGE LEARNING: PERSONALIZED TUTORING AND REAL-TIME FEEDBACK - Karimova Maftuna Rakhmon qizi (PEDAGOGS, 2025)
Abstract: This article explores the role of conversational AI tools, such as ChatGPT, in enhancing language learning. With the rise of artificial intelligence in education, AI-powered tools provide personalized, real-time feedback and language practice, which are essential for effective language acquisition. This study examines the benefits of using ChatGPT for language learning, focusing on its ability to offer dynamic interaction, immediate feedback, and tailored lessons based on individual learner needs. The findings suggest that AI tools like ChatGPT significantly contribute to learners’ language development, offering a more interactive and customized learning experience. The study also compares the effectiveness of AI-powered language learning with traditional methods, highlighting both strengths and limitations. Ultimately, this research sheds light on the transformative potential of conversational AI in language education and offers insights into its future integration into language classrooms.